Contesting Platform Power: The oppositional affordances of data activism - Papa, Venetia (My University, 2025)
Contesting Platform Power explores the practices and discourses of data activists, by shifting the focus from critical digital studies to critical platform studies through the theoretical lens of affordances, to understand the material means by which activist’s software and applications strives to empower users through data control. Papa critically explores the ways platform affordances, actions associated to the features of the platform which might be hidden or perceptible to the user, can create the possibilities for both action and constraint, but it ultimately rests upon users to either comply or resist. Platform affordances in this study are not to be conflated with specific features of the platform such as shares, clicks or reaction buttons, but refers the communicative practices and habits they allow or refuse to users within a technological space. An innovative contribution to the field of critical platform studies, chapters explore the theoretical underpinnings of affordances to sow the seeds for further critical analysis into the software and applications of data activists, while also suggesting a new typology that can aid researchers in identifying and analysing such practices. Featuring case studies of data activists’ examples, Papa demonstrates that such efforts can be used in a tactical manner by users to counter the hegemonic power of corporate platforms and AI. Chapter 1. Introduction: Untangling Platform Power and Data Activism Chapter 2. Enacting the Everyday: The Dialectic of Algorithms, Data activism, and Platform Power Chapter 3. Theorizing the Mediating Role of Affordances within the Terrain of Data Activism Chapter 4. Cartography of Data Activism Software and Applications Chapter 5. Empowering Resistance: Discourses and Dynamics of Activists Chapter 6. Agency, Tools and Imaginaries of Data Activism Chapter 7. Counter-AI activism tools Chapter 8. Conclusion: The Future of Platform Power and Data Activism